2015
DOI: 10.1111/asap.12091
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Links between Women's Business Ownership and Empowerment among Maasai Women in Tanzania

Abstract: Despite increasing interest and effort to support women's empowerment globally, women remain a severely disadvantaged group in nearly every country throughout the globe. In the current study, we examine the relationship between women's participation in financial markets and different indices of empowerment. Questionnaires were administered to three groups of Maasai women (N = 224) living in rural, northern Tanzania: women who were members of cooperatively owned business groups, women who owned businesses indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 51 publications
0
45
0
6
Order By: Relevance
“…Previous research has stressed the need to address the structural base of gender inequities and to take cultural norms into account (e.g., Connell, ; Dutt et al, ). In the current research, the training aimed to stimulate joint goal setting among couples with the aim to change gender roles with respect to their income‐generating activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has stressed the need to address the structural base of gender inequities and to take cultural norms into account (e.g., Connell, ; Dutt et al, ). In the current research, the training aimed to stimulate joint goal setting among couples with the aim to change gender roles with respect to their income‐generating activity.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying gendered power imbalances were not addressed. To stimulate gender equity, attention should be given to the root sources of the gendered power imbalances and manifestations of gender roles in local contexts (e.g., Dutt et al, ; Pratto & Walker, ). To the best of our knowledge, only one longitudinal field experiment investigated the impact of a gender and business training (focussing on the specific role of female entrepreneurs [gendered power imbalances, gender roles] and business skills) and the impact of inviting husbands to join this training on female borrowers' empowerment (Huis et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Men traditionally make investments in larger expenditures. If women gain power over these decisions, this is indicative of greater empowerment (e.g., Dutt et al ., ; Johnson, ). However, men’s controlling behaviour over their wives is one of the most apparent barriers to women’s empowerment (Dutt et al , ; Grabe et al , ; Kabeer, ).…”
Section: Defining Women’s Empowermentmentioning
confidence: 99%
“…Previous research showed that men’s controlling behaviour influenced different aspects of women’s empowerment. More precisely, husband’s controlling behaviour (e.g., allowing women to visit family and friends) was negatively related to self‐esteem and positively to physical violence and depression among women business owners in Tanzania (Dutt, Grabe, & Castro, ). Similar results were found among women landowners in Nicaragua and Tanzania showing that husbands controlling behaviour was positively related to women’s experience of physical and psychological violence (Grabe et al , ).…”
Section: Defining Women’s Empowermentmentioning
confidence: 99%
See 1 more Smart Citation